Web to World: Predicting Transitions from Self-Diagnosis to the Pursuit of Local Medical Assistance in Web Search - White, Ryen W.; Horvitz, Eric (American Medical Informatics Association, 2010)
Many people turn to the Web for self-diagnosis and healthcare assessment based on limited knowledge of signs, symptoms, and disorders. Studies of search and browsing for healthcare information have shown that reviewing Web content can lead to escalations from concerns about common, typically benign symp-toms to searches on rare and frightening disorders. We explore the potential for the Web to induce costly and potentially unnecessary engagements with health professionals. We present findings on the transition of search on common symptoms to the pursuit of in-world healthcare resources such as nearby physi-cians and healthcare facilities. We build models that predict the transition from searches on initial com-mon symptoms to queries pursuing local medical expertise, using evidence about a user’s stream of queries, the content on reviewed pages, and long-term medical search behaviors. Our findings have implications for reducing costly and unnecessary healthcare resource utilization through refinements of ranking algorithms and search interfaces.